Путешествие по России: стихи, [баллады, поэмы, песни, поэтические эпопеи в авт. ред.] / Владимир Тяптин - Тяптин Владимир Яковлевич (Проект, 2014)
Экземпляры: Аб (20141208) / Инвентарный номер: 101884 / Цена: 180.91 / Авт.знак: Т 99 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)